Evaluation of Students' Perceptions of Online-Based Science Learning Materials During The Covid-19 Pandemic at SMP IT Khairunnas, Bengkulu City - Ega Arya Saputra; Ikmi Marlina; Nur Azizah; Ogi Saputra; Ahmad Walid (Acitya: Journal of Teaching and Education, 2022)
This study aims to determine the perception of students' understanding of science material at SMP IT KHAIRUNNAS Bengkulu City during the covid-19 pandemic or during face-to-face learning. The method used in this research is using a qualitative method. The data analysis technique used is descriptive qualitative technique. The results showed that students' perceptions of science learning during the covid 19 pandemic at SMP IT KHAIRUNNAS Bengkulu City showed that on average students were more aware of learning during face-to-face learning compared to online learning, because online learning was considered difficult because the science material presented by the teacher was lacking. Obviously, students also have difficulty understanding the formula from the explanation without being written directly by the teacher on the blackboard, when face-to-face learning makes it easier to explain material and answer questions given by the teacher.